Chemometrics tools to distinguish wild and farmed meagre (Argyrosomus regius) - Chaguri, Milena Penteado [UNESP]; Maulvault, Ana Luísa; Costa, Sara; Gonçalves, Amparo; Nunes, Maria Leonor; Carvalho, Maria Luisa; Sant'ana, Léa Silvia [UNESP]; Bandarra, Narcisa; Marques, António (Hindawi, 2017)
Techniques to trace geographical origins and production methods are still scarce and not routinely applied by food safety authorities. The aim of this study was to assess the effectiveness of proximate chemical composition, fatty acid profile, macro and trace element content, and stable isotope ratios to distinguish wild (WM) and farmed (FM) meagre. There were differences in total lipids, some fatty acids (C16:2n-4, C16:4n-3, C18:0, C18:1n-9, C18:2n-6, C18:3n-3, C20:1n-9, C22:1n-11, C20:4n-6, C22:5n-6, and DHA), some macro and trace elements (Cl, S, Fe, Zn, Se, and Br), and δ13C and δ15N stable isotopes contents between FM and WM. Additionally, some fatty acids (e.g., linoleic) and elements (e.g., Cl, Fe, Br, and Rb) significantly differed between large and small FM. Therefore, it is possible to differentiate between FM (large and small specimens) and WM based on these compounds. The results of this study emphasize effectiveness of chemometrics tools for seafood traceability purposes. Practical applications: In recent years consumers are seeking healthy foods and increasingly discerning regarding food they will consume, however, consumers often do not find the information they seek. Thus, the fish authenticity is important requirements to ensure quality, provide adequate security controls and develop effective regulations. Food traceability includes food components identification to verify the compliance with labeling to prevent fraud. Fish industry must be providing information in the label about species, origin, age, and production systems. Therefore, there is an urgent need to develop methods to rapidly and accurately identify food that can help the authorities and fish industries to comply with the requirements for labeling and traceability, and to ensure product quality and consumer protection. This work was developed due to the need to establish functional techniques for fish discrimination. Techniques used in this study were effective in differentiation of meagre, which is one of the best candidates for large-scale aquaculture in Europe. Other works such as species determination of high commercial value, seasonality, and capture sites differentiation are being developed by our group.